Antisense Oligonucleotide-mediated Suppression of Muscle Glycogen Synthase 1 Synthesis as an Approach for Substrate Reduction Therapy of Pompe Disease - Nicholas P Clayton; Carol A Nelson; Timothy Weeden; Kristin M Taylor; Rodney J Moreland; Ronald K Scheule; Lucy Phillips; Andrew J Leger; Seng H Cheng; Bruce M Wentworth (Elsevier, 2014)
Pompe disease is an autosomal recessive disorder caused by a deficiency of acid α-glucosidase (GAA; EC 3.2.1.20) and the resultant progressive lysosomal accumulation of glycogen in skeletal and cardiac muscles. Enzyme replacement therapy using recombinant human GAA (rhGAA) has proven beneficial in addressing several aspects of the disease such as cardiomyopathy and aberrant motor function. However, residual muscle weakness, hearing loss, and the risks of arrhythmias and osteopenia persist despite enzyme therapy. Here, we evaluated the relative merits of substrate reduction therapy (by inhibiting glycogen synthesis) as a potential adjuvant strategy. A phosphorodiamidate morpholino oligonucleotide (PMO) designed to invoke exon skipping and premature stop codon usage in the transcript for muscle specific glycogen synthase (Gys1) was identified and conjugated to a cell penetrating peptide (GS-PPMO) to facilitate PMO delivery to muscle. GS-PPMO systemic administration to Pompe mice led to a dose-dependent decrease in glycogen synthase transcripts in the quadriceps, and the diaphragm but not the liver. An mRNA response in the heart was seen only at the higher dose tested. Associated with these decreases in transcript levels were correspondingly lower tissue levels of muscle specific glycogen synthase and activity. Importantly, these reductions resulted in significant decreases in the aberrant accumulation of lysosomal glycogen in the quadriceps, diaphragm, and heart of Pompe mice. Treatment was without any overt toxicity, supporting the notion that substrate reduction by GS-PPMO-mediated inhibition of muscle specific glycogen synthase represents a viable therapeutic strategy for Pompe disease after further development.